Critical Analysis of Family Warmth, Love, and Women's Struggles in Little Women - Yullyn Kestty Howay; Feraningsih Ethany Hegemur (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study presents a critical analysis of Little Women by Louisa May Alcott, focusing on the themes of family warmth, love, and women’s struggles as reflected in the experiences of the March sisters. The study aims to examine how characterization, conflict, and thematic development in the novel represent women’s identity, independence, and social expectations. This research employs a qualitative descriptive approach using literary analysis to interpret narrative elements such as characterization, plot development, themes, and moral messages in the novel. The analysis focuses on the four main characters Meg, Jo, Beth, and Amy whose personalities and life choices illustrate the process of personal growth from adolescence to adulthood in the midst of economic hardship and social limitations. The findings show that Jo March symbolizes women’s independence and resistance to traditional gender roles, while the other sisters reflect different aspects of responsibility, sacrifice, and emotional maturity. The conflicts in the story develop through family challenges, differences in character, romantic relationships, and experiences of loss, particularly the death of Beth, which strengthens the theme of family solidarity. The study also reveals that the novel conveys moral values such as perseverance, empathy, responsibility, and the importance of family relationships. Furthermore, the narrative highlights feminist perspectives by portraying women’s efforts to determine their own futures despite social restrictions. This study contributes to literary studies by providing a deeper understanding of how Little Women represents women’s struggles, personal identity, and family values, demonstrating the continued relevance of the novel in contemporary discussions about gender roles and women’s empowerment.